A growing number of cities worldwide are using the Milan Urban Food Policy Pact Monitoring and City Region Food System Indicator Framework to strengthen their food policy implementation - CGIAR Research Program on Water, Land and Ecosystems (2021)
WLE/RUAF, working with FAO and three pilot cities, developed and tested a handbook and resource pack to help cities implement the Milan Urban Food Policy Pact (MUFPP) monitoring framework.The pilot cities –Quito, Peru; Antananarivo, Madagascar; and Nairobi, Kenya – are continuing to develop their monitoring. More cities are now using the handbook, including Ede in the Netherlands and New Haven in the United States. This monitoring framework will also be the basis for ongoing and new FAO and CGIAR programs.